The effects of macronutrient composition of the larval diet on life history traits and pigmentation in Drosophila virilis - Rodrigues, Marisa Almeida (2014)
Tese de mestrado. Biologia (Biologia Evolutiva e do Desenvolvimento). Universidade de Lisboa, Faculdade de Ciências, 2014